Assessing delays in primary percutaneous coronary intervention for ST-segment elevation myocardial infarction patients at a tertiary care hospital in Sri Lanka: a retrospective cohort study - Gotabhaya Ranasinghe; Hasna Riyal; Kaveesha Perera; Anidu Pathirana; Theekshana Premawansha; Dinesh Ananthamoorthy; Sanduni D Gunarathne (BMJ Open)
Objectives To analyse patient profiles, transportation patterns and time delays in ischaemic time and door-to-balloon (DTB) time and evaluate the effect of these delays on in-hospital mortality among patients undergoing primary percutaneous coronary intervention (P-PCI) for ST-segment elevation myocardial infarction (STEMI) at a tertiary care hospital in Colombo.Design Retrospective observational study.Setting Tertiary care hospital specialising in STEMI treatment, located in Sri Lanka.Participants The study included adults aged 16–87 years admitted for P-PCI between January 2018 and September 2023, presenting with STEMI and undergoing emergency P-PCI. Patients with incomplete records or unrealistic values on ischaemic time or DTB time were excluded.Outcome measures Outcome measures include ischaemic time, DTB time and in-hospital mortality. The associations of demographic factors, transfer methods and DTB time with survival rates were analysed.Results A total of 1758 patients underwent P-PCI (mean age, 53.0±11.64), with 85.2% being male. The male risk group was 46–60 years (OR, 1.22), whereas the female risk group was predominantly older than 60 years (OR, 1.87). The median ischaemic time was 4 hours and 36 min, and the median DTB time was 110 min. The in-hospital mortality rate was 3.8% (63/1,664). Prolonged DTB times exceeding 120 min were significantly associated with increased mortality (p=0.046), although alternative thresholds (45, 60 or 90 min) were not significant (p>0.05). Binary logistic regression with multiple variables identified female sex (OR, 2.52; 95% CI, 1.168 to 5.435, p=0.018), increasing age (OR 1.05; 95% CI, 1.016 to 1.085, p=0.004) and DTB times (OR, 1.001; 95% CI, 1.000 to 1.002, p=0.027) as independent predictors of mortality.Conclusions Despite improvements in DTB times, this study indicates that prolonged delays exceeding 120 min remain associated with increased mortality. Older age and female sex were identified as independent predictors of higher mortality. These findings underscore the need for efficient patient transfer methods and prompt decision-making at the primary healthcare level to minimise delays and disparities in P-PCI outcomes.